PENGARUH PAPARAN KEBISINGAN TERHADAP MORFOLOGI SPERMATOZOA MENCIT JANTAN (MUS MUSCULUS L) YANG DIBERIKAN EKSTRAK BIJI ANGGUR (VITIS VINIFERA L.) - Zuhud Zinedine Pangindra, (2020)
Noise that exceeds the threshold value and is exposed continuously can increase Reactive Oxygen Species (ROS) and cause an increase in oxidative stress, thereby reducing the quality of spermatozoa. Grape seeds are known to contain polyphenols as an antioxidant effect. This study aimed to examine the effect of noise exposure on the morphology of spermatozoa in male mice given grape seed extract. Grape seed extract is expected to provide antioxidants to repair morphological damage due to these effects. This type of research was an experimental study with research methods using the post test only control group design, the research subjects were 28 male Swiss Webster mice divided into 4 groups: Groups A, B, C (treatment group) were given exposure to noise with sequential intensity of 65 dB, 85 dB, 105 dB, Group D (control group) were not given noise exposure and were given grape seed extract. The treatment was given for 33 days. Results were assessed after the treatment period by counting the number of abnormal spermatozoa in 100 spermatozoa. Statistical tests using Anova and Post Hoc LSD. From this study it was found that exposure to noise with different intensities of 65 dB, 85 dB, 105 dB could improve the abnormal morphology of spermatozoa of male Swiss Webster mice given grape seed extract by showing all groups given noise exposure had significant significance to the control group of ( p = 0,000)